Optimisation of plating parameters and performance analysis of black chromium coating for solar thermal energy applications - Yahya, Nizamil Fairuz (2001)
Black chromium coating (BCC) is well known to give high performance in absorbing high solar radiation and low emittance in solar spectrum near infrared region. Different composition and plating parameters of the black chromium solution will give various combinations of the coating optical property and performance. The purpose of this study is to determine the optimum plating parameters using the coating solutions, which had been modified by the current work, in order to improve the optical properties and the performance of the coating. The coatings were produced from fluoride and borate baths. Newly improved fluoride baths have better throwing power and have the potential for shorter plating time from 2 to 6 minutes with excellent black coating compared to borate baths which have higher plating time from 4 to 10 minutes which is powdery and dull black in colour. It was also found that the absorptance (a) and emittance (E) values of the coating that were determined by scanning infrared spectrophotometer technique were affected by the plating parameters. The plating parameters such as plating time, bath temperature and current density, affect the grain size and distribution of surface morphology which were observed under scanning electron microscope. Coating performance which is determined by using differential thermal analyser, humidity-thermal cycle cracking, sunshine weather-ometer and salt spray tests, shows that improved fluoride black chromium coating is better than borate black chromium coating. The coating gives good thermal stability at temperature around 1300 C , excellent humidity, resistance to weather and corrosion and good coating adhesion. It is found that the coating performance is dependent on the plating parameters for both newly improved baths that should be kept between its parameter limits in order to produce good chromium coating for solar thermal application.